2021
DOI: 10.1128/msystems.01045-21
|View full text |Cite
|
Sign up to set email alerts
|

Short-Chain Fatty Acids Reduced Renal Calcium Oxalate Stones by Regulating the Expression of Intestinal Oxalate Transporter SLC26A6

Abstract: Some studies found that the relative abundances of short-chain-fatty-acid (SCFA)-producing bacteria were lower in the gut microbiota of renal stone patients than healthy controls. Our previous study demonstrated that SCFAs could reduce the formation of renal calcium oxalate (CaOx) stones, but the mechanism is still unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 53 publications
(67 reference statements)
0
16
0
Order By: Relevance
“…The bacterial communities are distinct with an enrichment of the genera Akkermansia, Klebsiella and Enterobacteriaceae and a depletion of the genera Blautia and Roseburia in patients with non-hemodialyzed CKD. Some functions are predicted upward such as the metabolism of tryptophan and phenylalanine and others are predicted downward such as the metabolism of arginine and proline during CKD [ 115 , 116 ]. Patients with end-stage kidney disease on peritoneal dialysis were less likely to have Bifidobacterium catenulatum, Bifidobacterium longum, Bifidobacterium bifidum, Lactobacillus plantarum, Lactobacillus paracasei and Klebsiella pneumoniae than healthy controls [ 117 ].…”
Section: Pet Dog and Human Gut Microbiota In Disease Conditionsmentioning
confidence: 99%
“…The bacterial communities are distinct with an enrichment of the genera Akkermansia, Klebsiella and Enterobacteriaceae and a depletion of the genera Blautia and Roseburia in patients with non-hemodialyzed CKD. Some functions are predicted upward such as the metabolism of tryptophan and phenylalanine and others are predicted downward such as the metabolism of arginine and proline during CKD [ 115 , 116 ]. Patients with end-stage kidney disease on peritoneal dialysis were less likely to have Bifidobacterium catenulatum, Bifidobacterium longum, Bifidobacterium bifidum, Lactobacillus plantarum, Lactobacillus paracasei and Klebsiella pneumoniae than healthy controls [ 117 ].…”
Section: Pet Dog and Human Gut Microbiota In Disease Conditionsmentioning
confidence: 99%
“…Microbiota is important in the development of urolithiasis. Several studies have reported the effect of microbiota in preventing urinary stone through its metabolites, SCFAs [ 59 ].…”
Section: Short Chain Fatty Acidmentioning
confidence: 99%
“…Their metabolites were mainly SCFAs [ 72 ]. In an experiment using mice, administration of SCFA reduced the formation of CaOx crystals in kidneys and urinary oxalate levels, but increased SCFA-producing bacteria and SCFA in the colon [ 73 ].…”
Section: Substances Involved In Crosstalkmentioning
confidence: 99%